CAPTURE FISHERIES BUSINESS ANALYSIS OF THE TROLL LINE FISHING FLEET AT THE PALABUHANRATU ARCHIPELAGO FISHING PORT, SUKABUMI, INDONESIA - Faqih Baihaqi; Shafira Bilqis Annida (Jurnal Perikanan Unram, 2024)
The troll line fishing fleet is one of several capture fisheries business units often found at the Palabuhanratu Archipelago Fishing Port, Sukabumi, Indonesia. The Sukabumi Central Capture Fisheries Statistics Agency noted a decrease in trolling boats catching and landing fish at the Palabuhanratu Archipelago Fishing Port in the last ten years. This condition allegedly indicates a decline in income for the capture fisheries business players. This research evaluated the net income value of the catch fisheries business unit of the troll line fishing fleet at the Palabuhanratu Archipelago Fishing Port. Data was collected using survey and interview methods from January to March 2023. The purposive sampling method highlighted that 15 respondents consisting of ship owners, captains, and crew members of fishing boats were appointed as sources for this research. Analysis of the fishing business of the Troll Line fishing fleet evaluates the average net income value as 636,496,667 IDR/vessel/year. This net income value is distributed among seven business actors consisting of ship owners (317,596,429 IDR/year), a captain (95,278,929 IDR/year), and four crew members (55,579,375 IDR/person/year). The evaluation value of net income indicates that the fisheries business unit caught by the troll line fishing fleet at the Palabuhanratu Archipelago Fishing Port still has quite promising profits for all business actors.